Prevalence and impact of self‐reported painful and non‐painful constipation in the general population. Issue 4 (23rd January 2020) - Pannemans, Jasper; Van den Houte, Karen; Fischler, Benjamin; Piessevaux, Hubert; Carbone, Florencia; Tack, Jan
Abstract: Introduction: Chronic constipation, defined by the Rome IV criteria, is a highly prevalent functional bowel disorder with major overlap with other bowel disorders. Therefore, a pooled‐analysis to evaluate the presence of self‐reported constipation in the general population was conducted. Further, its association with other bowel symptoms and its health‐economic impact was analyzed. Methods: Collection of information on bowel symptoms' prevalence and their impact was done through an Internet survey (Medistrat Internet panel). The analysis focused on patients who reported constipation symptoms over the last 12 months. Firstly, participants who with or without constipation were compared. Secondly, subjects reporting constipation with (PC) or without abdominal pain (NPC) were studied. Key Results: A total of 1012 subjects (45.2 ± 0.5 years old, 62% females), of whom 217 (21%) reported constipation, completed the survey. Women were significantly more represented in the group reporting constipation compared to those with other bowel symptoms (81.57% vs 56.60%, P  < .0001). Subjects reporting constipation experienced more additional bowel symptoms than those who did not report constipation [3(2‐6) vs 2(1‐4), P  < .0001]. Of those with constipation, 134 patients reported NPC compared to 83 patients with PC. The presence of PC was associated with higher prevalence of diarrhea symptoms, alternating bowel movements, bloating, cramps, gas, and altered stool frequency and consistency (all P  < .01). Out of 83 PC patients, 38 (45.24%) fulfilled the Rome IV IBS criteria. Conclusion: Self‐reported constipation, often associated with other bowel symptoms, is a highly prevalent condition in the Belgian general population. Especially when abdominal pain is present, this generates major healthcare costs. Abstract : Patients with painful constipation were less likely to point constipation as their most bothersome symptom, reflecting that asking a patient's most bothersome symptom in a clinical setting allows useful further classification. Further as shown by the graph, patients with painful constipation often have more total bowel symtoms than patients with nonpainful constipation.